1985
DOI: 10.1080/14640748508401177
|View full text |Cite
|
Sign up to set email alerts
|

Contingency Effects with Maintained Instrumental Reinforcement

Abstract: In three experiments we investigated the effect on the performance of thirsty rats of varying the instrumental contingency between lever pressing and the delivery of a saccharin reinforcer. In Experiment 1, the subjects performed more slowly in a non-contingent condition, in which the momentary probability of reinforcement was unaffected by whether or not the animals pressed, than in a contingent condition in which the reinforcer was never presented except following a lever press. This was true of performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
101
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 24 publications
6
101
0
Order By: Relevance
“…Nonveridical performance and judgments can also be induced by contingency manipulations. Both Dickinson and Charnock (1985) and Hammond and Weinberg (1984) found that signaling noncontiguous reinforcers under a noncontingent schedule augmented the instrumental performance of rats. A corresponding illusion of control was induced in human causality judgment by Shanks (1989), using the same signaling operation.…”
Section: Discussionmentioning
confidence: 99%
“…Nonveridical performance and judgments can also be induced by contingency manipulations. Both Dickinson and Charnock (1985) and Hammond and Weinberg (1984) found that signaling noncontiguous reinforcers under a noncontingent schedule augmented the instrumental performance of rats. A corresponding illusion of control was induced in human causality judgment by Shanks (1989), using the same signaling operation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigators (e.g., Balsam, 1985;Dickinson & Charnock, 1985;Matzel, Brown, & Miller, 1987) have reported that nonreinforced exposure to an excitatory context enhances the CR to a CS previously trained in that context. However, the inverse relationship has not typically been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, associative learning not only increases with the probability of the second event (E 2 ) given the first event (E 1 ), or in other words with the likelihood of contiguous pairings of E 1 and E 2 , but also decreases with the likelihood of E 2 in the absence of E 1 (e.g. [9,10]). Given that the stimulus and response function as the two events E 1 and E 2 , respectively, in sensorimotor learning, an associative account predicts that this form of learning should increase with P(R/S) but decrease with P(R/-S).This sensitivity to contingency is captured by, among others, the Rescorla-Wagner model of associative learning [24].…”
Section: Introductionmentioning
confidence: 99%